Ehrenamtlich aktive Frauen im Natur- und Umweltschutz. - Schönfeld, Fiona Luise Désirée (My University, 2014)
Die Arbeit untersucht das ehrenamtliche Engagement von Frauen in Natur-/Umweltschutzorganisationen. Durch qualitative Inhaltsanalyse von leitfadengestützten biografischen Interviews mit 30 Frauen, die sich aktiv in Bayern engagieren, wird eine Typologie "weiblicher" Ehrenamtsbiografien entwickelt. Weitere Forschungsfragen behandeln den sozialen und thematischen Handlungskontext des Ehrenamts und wahrgenommene geschlechtsbezogene Barrieren.

This study explores volunteering of women in environmental organisations. Guided biographical interviews with 30 women volunteering actively in Bavaria/Southern Germany are used to collect data. Qualitative content analysis is applied for data analysis. A typology of female voluntary biographies is developed. Further research questions address the individual social and thematic context of volunteering as well as the perception of gender barriers.
Volunteering of women in environmental organisations. A qualitative study of biographies, concepts and gender barriers.
Keywords: Partizipation; Frau; Naturschutz; Umweltschutz; Organisationen; Befragung; Ehrenamt; Bürgerschaftliches Engagement; Biographie; Genderforschung